PELAKSANAAN PERJANJIAN JUAL BELI MENGGUNAKAN SISTEM IJON ANTARA PETANI KELAPA DENGAN TAUKE DI KECAMATAN TEMPULING - Ulfasari, Sofiya; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Most of the people of Sungai Salak Village, Tempuling Subdistrict work as farmers. Farming incoconut groves is the biggest choice because of this region. The crops are sold using the bonded system,namely the debt repayment system with these harvests that have been carried out for generations by thecommunity in Sungai Salak Village. Farmers who owe to the tauke must make debt payments to the tauke,namely by cutting the coconut payment from the tauke to the farmers, deducted from the sale of theircoconut harvest at a low price. using a bonded system between coconut farmers and a tauke in TempulingSubdistrict, Indragiri Hilir Regency has given justice or injustice between the two parties. Second, to find aresolution so that the implementation of a sale and purchase agreement using the bonded system givesjustice.This type of research can be classified into the type of juridical social research, because in thisstudy the author immediately conducts research on the location or place under study in order to provide acomplete and clear picture of the problem under study.Based on the results of the problem research there are two main things that can be concluded.First, unequal rights and obligations where the cheap price of coconut for the price of coconut that is set isRp. 1,800 to Rp. 2,300, - the price is below the market price of coconut in Indragiri Hilir which is Rp. 3,810/ kilogram. Farmers do not participate in determining coconut tariffs. Second, the Resolution for theImplementation of the Sale and Purchase Agreement Using this Bonded System Gives Justice This is that itwould be good for the Government to study in other countries that have succeeded in overcoming injusticedue to the implementation of agreements like this. regulated in regulations in the form of laws or higherregulations. Author's suggestion, First, there needs to be a special regulation made by the governmentregulating the implementation of a sale and purchase agreement using the bonded system. For the positionof both the farmer and the tauke to be equally strong and the rights and obligations carried out properly andcorrectly. Second, optimizing Law No.19 of 2013 concerning the Protection and Empowerment of Farmers.In order to create awareness from the community, especially farmers, not to start participating in theimplementation of the sale and purchase agreement with the bonded system by conducting counseling andeducation on agriculture and counseling about saving and establishing cooperatives.Keywords: Coconut Buy and Sell - Ijon System - Tempuling District